Effects of Electronic Detonators in Underground Tunneling Applications - Charles Zdazinsky (International Society of Explosives Engineers, 2015)
Over-break is undesirable in underground civil construction because it excessively damages rock along the perimeter of the tunnel, which directly influences the cycle times of advancement. A quicker cycle time for each process is required to optimize the operation and therefore minimizing over-break is essential for operational success.